2015
DOI: 10.4236/ojcm.2015.53011
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement in the Electrical and Thermal Properties of Ethylene Vinyl Acetate (EVA) Co-Polymer by Zinc Oxide Nanoparticles

Abstract: EVA/ZnO nanocomposites of 1%, 2% and 4% ZnO were fabricated by direct probe sonicator method. The ZnO nanopowders were prepared by solvothermal method. As the particle size of the filler incorporated to the polymer matrix decreases, the properties of the polymer-filler interface show dominance over its bulk properties. The dielectric constant and dielectric loss of the composites at ambient temperatures are found to decrease with increasing frequency. The thermal analysis using TGA-DTA is also performed and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Similar studies that used another kind of polymers were also performed by Diez-Pascual et al, 24,25 Feng et al, 26 Celebi et al, 27 Sebastian et al, 28 Mostafaei et al, 29 Batool et al, 30 Ma et al, 31 and Azizi et al 32 In these works, mechanical, thermal, electrical, optical, and antibacterial properties of polymer-ZnO nanocomposites were studied. In some of these studies, it is shown that ZnO as a filler causes same increase in the mechanical and thermal properties of some polymers, [27][28][29][30] while in some of these studies, it causes some decrease in the thermal properties of some polymers. 31,32 In all studies referenced above, ZnO nanoparticles were used as fillers, i.e., previously synthesized ZnO nanoparticles were doped into polymers.…”
Section: Introductionmentioning
confidence: 67%
“…Similar studies that used another kind of polymers were also performed by Diez-Pascual et al, 24,25 Feng et al, 26 Celebi et al, 27 Sebastian et al, 28 Mostafaei et al, 29 Batool et al, 30 Ma et al, 31 and Azizi et al 32 In these works, mechanical, thermal, electrical, optical, and antibacterial properties of polymer-ZnO nanocomposites were studied. In some of these studies, it is shown that ZnO as a filler causes same increase in the mechanical and thermal properties of some polymers, [27][28][29][30] while in some of these studies, it causes some decrease in the thermal properties of some polymers. 31,32 In all studies referenced above, ZnO nanoparticles were used as fillers, i.e., previously synthesized ZnO nanoparticles were doped into polymers.…”
Section: Introductionmentioning
confidence: 67%
“…The relation between dielectric loss tangent and frequency for all samples is shown in Figure 7 b. In the lower frequency region, there was a more significant dielectric loss due to the loss associated with ionic mobility [ 43 ]. The high dielectric loss tangent occurred in all samples except the EVA film whose functional groups mainly comprised amide groups with high polarizability in TPU.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, a few will be active in a material having low relative permittivity. In ZnO, all the four types of polarizations exist but the active one is dependent on the frequency of operation [33][34][35][36][37] e origin of high k in a material at low frequencies is the presence of all four sources of polarization, and it starts decreasing with the increase in frequency since dipoles in the material cannot follow the high frequency of applied field [38]. e value of k in a material increases with the increase in temperature which is attributed to the fact that a greater number of frozen dipoles are liberated due to thermal energy [39].…”
Section: Source Of Polarizationmentioning
confidence: 99%